2020
DOI: 10.1175/jamc-d-19-0209.1
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Variability in Dynamically Downscaled Simulations of Alaska’s Present and Future Summer Climate

Abstract: Lightning is a key driver of wildfire activity in Alaska. Quantifying its historical variability and trends has been challenging because of changes in the observational network, but understanding historical and possible future changes in lightning activity is important for fire management planning. Dynamically downscaled reanalysis and global climate model (GCM) data were used to statistically assess lightning data in geographic zones used operationally by fire managers across Alaska. Convective precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
(76 reference statements)
1
23
0
Order By: Relevance
“…A significant upgrade to the system in 2000 led to an increased detection accuracy and efficiency of 0.5 -2 km and 80 -90 %, respectively 46 . The replacement of the Impact lightning system with a Time of Arrival (TOA) system in 2012 resulted in a further 1.5-fold increase in the detection efficiency, and an increased accuracy stemming from the counting of strokes per flash instead of lightning flashes 48 .…”
Section: Methodsmentioning
confidence: 99%
“…A significant upgrade to the system in 2000 led to an increased detection accuracy and efficiency of 0.5 -2 km and 80 -90 %, respectively 46 . The replacement of the Impact lightning system with a Time of Arrival (TOA) system in 2012 resulted in a further 1.5-fold increase in the detection efficiency, and an increased accuracy stemming from the counting of strokes per flash instead of lightning flashes 48 .…”
Section: Methodsmentioning
confidence: 99%
“…To place the WGLC in the context of other widely used lightning data, we compared our gridded fields with two datasets based on ground-based detection networks and one from spaceborne remote sensing. We used raw stroke count data from the Alaska Lightning Detection Network (ALDN; Fronterhouse, 2012) for the years 2012-2019 and a gridded product based on https://doi.org/10.5194/essd-2021-89 Studies have shown that the detection efficiency of the ALDN increased from 40-80% to 80-90% after sensors were upgraded to Vaisala Impact ES sensors in 2012 (Bieniek et al, 2020;Farukh et al, 2011). A further upgrade to a completely new set of time-of-arrival sensors (operated by TOA Systems, Inc.) was made after 2012 (Bieniek et al, 2020 Coordination Center, 2021) from the beginning of the period for which the TOA-based sensor network was operational (2012-2019).…”
Section: Comparison With Independent Observations Of Lightning Occurrmentioning
confidence: 99%
“…Under future climate change, an overall increase in fires is expected in the Arctic Council region, indicating that associ-ated emissions are also likely to increase. For instance, natural fires, defined as lightning-caused fires, may increase as lightning is predicted to increase (Púčik et al, 2017;Veraverbeke et al, 2017;Bieniek et al, 2020), under Representative Concentration Pathways (RCPs) 4.5 (stabilizing emissions) and 8.5 (high emissions) developed for the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5). Likewise, using the same scenarios, wildfire emissions of BC, CO, NO x , PM 2.5 , and SO 2 could exceed anthropogenic emissions in northeastern Europe, including Sweden and Finland, by 2090 (Knorr et al, 2016).…”
mentioning
confidence: 99%